Game Zep Quiz as a Media for Evaluation of Social Studies Learning at SMPN 37 Samarinda to Improve Spatial Intelligence - Hidayah, Ainur; Setyasih, Iya' (Dinasti International Journal of Education Management and Social Science, 2025)
The use of game-based evaluation media is necessary to increase student engagement and support the development of spatial intelligence in social studies learning. This study aims to analyze the use of the Zep Quiz Game as an evaluation medium for social studies learning and to determine the response of eighth-grade students at SMP Negeri 37 Samarinda to its application. This study used a quantitative approach with a comparative descriptive design combined with a one-cycle action research, involving 152 students through a total sampling technique. Data were collected through spatial intelligence tests and student response questionnaires, then analyzed using descriptive statistics and one-way ANOVA tests at a significance level of 0.05. The results showed that the average spatial intelligence of students was in the fairly good category, with the highest achievement in the visualization indicator, and the students' responses were predominantly in the very good category. The ANOVA test results showed a significant difference in spatial intelligence between classes (p < 0.05), indicating that the effectiveness of using the Zep Quiz Game was influenced by class characteristics and student engagement levels. Overall, the Zep Quiz Game was effective as an interactive and meaningful medium for evaluating social studies learning.